Web-Based Household Cash Finance Application - Ach Nur Ardyansyah; Hindarto Hindarto (Universitas Muhammadiyah Sidoarjo, 2022)
Regulating financial management has become a problem that will be faced by every adult human being. To be able to manage finances well, every individual needs to learn to understand the design of cash inflows and outflows as a design of needs and wants. To make it easier to make this financial plan, various tools have been created. In this modern era, an application has become familiar among everyone. To make this application, there needs to be a research first. And after getting the results of the analysis, it was identified that with use that includes a small scale, the application should be simple and easy to use. With various basic features such as recording cash in, recording cash out and the most important is monthly reports that can be monitored. Applications for programming are sublime text 3, Xampp and databases from MySQL. This application runs on a web base so that it can be run universally by every individual.